Self Disclosure Santri Remaja di Media Sosial: Peran Self Identity Status dan Affiliation Motive - Fenti Hikmawati; Alida Nurawaliah; Ila Nurlaila Hidayat (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2021)
One of the most important developmental tasks for adolescents is to find self-identity. Some of the teenagers take education in Islamic boarding schools so that they have a special predicate as Islamic students or santri. For this reason, it is important to understand how the process of developing adolescent students in the formation of their identity status as Islamic students in the current modern era. This study aims to determine the effect of self identity status and affiliation motive on self disclosure in adolescent Islamic students. This study uses a quantitative correlational method with a total of 140 students was obtained through random sampling techniques. Data collection tools using self identity status scale, affiliation motive scale and self disclosure scale. The multiple linear regression analysis show that there is an influence of self identity status and affiliation motive on self disclosure on social media.